Effect of wet dressing of Chinese herbs on subcutaneous induration caused by subcutaneous injection of Azacitidine (中药湿敷改善阿扎胞苷皮下注射所致皮下硬结的效果观察) - ZHAO Jialu (赵佳璐); WANG Huaxin (王华新); LI Ye (李野) (中西医结合护理)
Objective To investigate the effect of wet dressing of Chinese herbs on subcutaneous induration caused by subcutaneous injection of Azacitidine. Methods Totally 50 patients with subcutaneous induration caused by subcutaneous injection of Azacitidine for the treatment of myelodysplastic syndrome were randomly divided into the observation group and the control group, with 25 cases in each group. The Mupirocin ointment was applied on the surface of subcutaneous induration in the control group, and wet dressing of Chinese herbs was applied in the observation group. The subsiding of subcutaneous induration, pain and swelling were observed. Results In the observation group, subcutaneous induration subsided in all patients, and there were 2 cases of pain and 4 cases of remained swelling. In the control group, subcutaneous induration subsided in 13 patients, and there were 6 cases of pain and 5 cases of remained swelling. Conclusion The wet dressing of Chinese herbs is effective to relieve the subcutaneous induration and related pain and swelling following ubcutaneous injection of Azacitidine. (目的 观察中药湿敷治疗阿扎胞苷皮下注射所致皮下硬结的应用效果。方法 将50例骨髓增生异常综合征(MDS)行阿扎胞苷皮下注射所致皮下硬结患者分为观察组和对照组, 各25例。对照组采用莫匹罗星(百多邦)软膏涂于皮下硬结处, 观察组采用中药湿敷。比较2组干预后皮下硬结消退以及疼痛和肿胀缓解情况。结果 观察组皮下硬结均消退, 仅2例患者存在不同程度的疼痛, 有4例患者肿胀未缓解; 对照组皮下硬结消退13例, 有6例患者存在不同程度的疼痛, 5例患者肿胀未缓解。结论 中药湿敷能有效改善阿扎胞苷皮下注射所致皮下硬结, 缓解疼痛与肿胀。)